MUTASI KERJA APARATUR SIPIL NEGARA: Job Transfer For State Civil Appartus - Melanie Putria Maharani Hartono; Andari Yurikosari (Reformasi Hukum Trisakti, 2025)
The job reassignment (mutasi) of Civil Servants (ASN), particularly in cases involving demotion, is one of the key instruments in personnel management, as regulated under the National Civil Service Agency Regulation Number 5 of 2019 and other relevant laws and regulations. The research problem focuses on the implementation of ASN job reassignments involving demotionspecifically whether such reassignments are based on the principle of justice as mandated by Indonesia’s positive law, and aims to identify the obstacles encountered in its execution. This study employs a normative legal method with statutory and case approaches, using secondary data as the primary source, which is analyzed qualitatively and concluded deductively. The findings indicate that ASN job reassignments, particularly those involving demotion, often fail to comply with existing regulations both in terms of employee welfare and adherence to administrative procedures. The main challenges identified include a lack of transparency in the process, disharmony between institutional policies, and decisions that are misaligned with the employees’ professional needs. To ensure a fair implementation of job reassignment, it is necessary to strengthen oversight mechanisms, clarify procedures, and provide legal protection for civil servants adversely affected by such decisions.